2021
DOI: 10.1097/jcma.0000000000000595
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 in pregnancy: Part I. Clinical presentations and untoward outcomes of pregnant women with COVID-19

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (coronavirus disease 2019, COVID-19) is a pandemic disease with rapidly and widely disseminating to the world. Based on experiences about the H1N1, Severe Acute Respiratory Syndrome (SARS) and Middle East Respiratory Syndrome (MERS) coronavirus pandemics, pregnant women who are infected are disproportionately more likely to develop severe illness and need more hospitalizations, intensive care, and finally die of diseases compared with those nonpregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 78 publications
0
31
0
Order By: Relevance
“…It is well known that pregnancy alters the immune system and its response to viral infection, and infection with coronavirus, in theory, could lead to more severe symptoms, especially in the third trimester [ 8 ]. One study found that the incidence of SARS-CoV-2 infection in pregnant women was 3.02 times greater than that in the general population [ 9 ], and Peng-hui Wang et al [ 10 ] pointed out that pregnant women with COVID-19 are more prone to develop severe conditions with a high mortality rate. Previous studies have shown that pregnant women infected with Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV) or Middle East Respiratory Syndrome Coronavirus had a higher risk of developing adverse complications.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that pregnancy alters the immune system and its response to viral infection, and infection with coronavirus, in theory, could lead to more severe symptoms, especially in the third trimester [ 8 ]. One study found that the incidence of SARS-CoV-2 infection in pregnant women was 3.02 times greater than that in the general population [ 9 ], and Peng-hui Wang et al [ 10 ] pointed out that pregnant women with COVID-19 are more prone to develop severe conditions with a high mortality rate. Previous studies have shown that pregnant women infected with Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV) or Middle East Respiratory Syndrome Coronavirus had a higher risk of developing adverse complications.…”
Section: Introductionmentioning
confidence: 99%
“…6 However, these newborns may be complicated by premature preterm labor, which has been dramatically increased in recent years. 7 The challenge is not only exacerbated by shortage of obstetricians and pediatricians, but also associated with a dramatically increasing heavy economic and social burden. 6 To achieve this goal, we are looking forward to seeing the authors' kind response.…”
Section: Dear Editormentioning
confidence: 99%
“…Critical meta-analysis studies have identified that pregnant women with CO-VID-19 are more asymptomatic than nonpregnant women of the same age group with COVID-19. However, these pregnant women with COVID-19 indicated a higher likelihood of fatal complications associated with the disease, resulting in a high mortality rate [4] [5].…”
Section: Introductionmentioning
confidence: 99%